Faktor Manusia Dengan Terjadinya Kecelakaan Kerja Di Sentra Industri Meubel Aluminium Di Kabupaten Hulu Sungai Utara - Michelle Savitri; Gunung Setiadi; Yohanes Joko Supriyadi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2016)
Abstract : Human Factors With The Occurrence Of Work Accidents In Industry Center Of Aluminium Furniture Regency Hulu Sungai Utara . Work accident do not happen by accident but there is. The first group is categorized the 80-85% of the human factor and 20-25% because to mechanical/environmental factors. Human factors that can lead to the occurrence of accidents is worker characteristics (age, education level, work period, and job training), less concentration workers, work discipline (APD) and psychological factors (marital status). The purpose of this analytic research is to know the relation of human factors with the occurrence of accidents. This type of research analytic with cross sectional design. Population of research to 43 people. Data analysis used X2 (Chi Square). The results showed that once a work accident. Many accident as 40 people. The type of accident is slipped (11.6%), punctured (48.8%), cut throat (32.6%). Location of the wound (69.8%). The results showed that there is a relationship of age and educational level (p <0.05) with the occurrence of accidents. Control means with makes a comfortable working space, rest enough schedule, procurement of personal protective equipment (PPE) in accordance with the hazard potential Keywords: human factors; occupational accidents; industry Aluminum furniture